The cultural construction of “executive function” - Ivan Kroupin; Helen Elizabeth Davis; Emily Burdett; Agustina Bani Cuata; Vahumburuka Hartley; Joseph Henrich (Proceedings of the National Academy of Sciences, 2025)
In cognitive science, the term “executive function” (EF) refers to universal features of the mind. Yet, almost all results described as measuring EF may actually reflect culturally specific cognitive capacities. After all, typical EF measures require forms of decontextualized/arbitrary processing which decades of cross-cultural work indicate develop primarily in “schooled worlds”–industrialized societies with universal schooling. Here, we report comparisons of performance on typical EF tasks by children inside, and wholly outside schooled worlds. Namely, children ages 5 to 18 from a postindustrial context with universal schooling (UK) and their peers in a rural, nonindustrialized context with no exposure to schooling (Kunene region, Namibia/Angola), as well as two samples with intermediate exposure to schooled worlds. In line with extensive previous work on decontextualized/arbitrary processing across such groups, we find skills measured by typical EF tasks do not develop universally: Children from rural groups with limited or no formal schooling show profound, sometimes qualitative, differences in performance compared to their schooled peers and, especially, compared to a “typical” schooled-world sample. In sum, some form of latent cognitive control capacities are obviously crucial in all cultural contexts. However, typical EF tasks almost certainly reflect culturally specific forms of cognitive development. This suggests we must decide between using the term EF to describe 1) universal capacities or 2) the culturally specific skill set reflected in performance on typical tasks. Either option warrants revisiting how we understand what has been measured as EF to date, and what we wish to measure going forward.